The «Function» of Criminal Prosecution - Baghdasaryan, Gevorg (Bulletin of Yerevan University C: Jurisprudence, 2025)
The article is devoted to the essence of criminal prosecution as a criminal procedural phenomenon. The author consistently analyzes the historical development of the legislative concept of criminal prosecution, as well as the theoretical debates that have significantly influenced its formation. The discussion then focuses on the question of whether criminal prosecution can be considered as an independent procedural function. In particular, analyzing the procedural actions attributed to the substance of criminal prosecution in the context of the main characteristics of a criminal procedural function, the author states that these actions in fact constitute elements of other areas of procedural activity. Therefore, criminal prosecution cannot be regarded as an independent activity, its type, or direction. Then, considering this issue within the framework of the right to fair trial and proceeding from the premise that public criminal procedural activity is aimed at establishing objective truth and does not have an accusatory nature, the author also excludes that establishing the accused’s guilt and ensuring their criminal liability may not be viewed as the mission of any participant in the proceedings. As a result of the analysis, the author concludes that criminal prosecution is not a procedural function, but rather a state of procedural relations formed as a result of the investigation, its organization, and the exercise of supervisory functions over it, which reflects the participation of the person suspected of committing the alleged offense in the criminal proceedings. According to the author, criminal prosecution arises from the moment a decision is made to initiate it and is not carried out as such, but continues to exist by virtue of its initiation and the absence of its termination, regardless of whether any actions aimed at proving the person’s guilt were taken during that period. Moreover, it persists even when actions are undertaken to refute the accused’s guilt.